2021
DOI: 10.3390/jcm11010185
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Development of Coagulopathy after Open Traumatic Brain Injury

Abstract: Background: The incidence of coagulopathy after open traumatic brain injury (TBI) is high. Coagulopathy can aggravate intracranial hemorrhage and further increase morbidity and mortality. The purpose of this study was to determine the clinical characteristics of coagulopathy after open TBI and its relationship with the prognosis. Methods: This study retrospectively evaluated patients with isolated open TBI from December 2018 to December 2020. Coagulopathy was defined as international normalized ratio (INR) >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The studies were assessed with appropriate guidelines to characterize their quality based on several criteria ( Table 1 ) [ 8 , 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. NOS scores of 7–9 were deemed sufficient for the study as it fell in the region of “high quality” study according to the NOS guidelines, including case-control studies.…”
Section: Resultsmentioning
confidence: 99%
“…The studies were assessed with appropriate guidelines to characterize their quality based on several criteria ( Table 1 ) [ 8 , 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. NOS scores of 7–9 were deemed sufficient for the study as it fell in the region of “high quality” study according to the NOS guidelines, including case-control studies.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic inflammatory markers such as NLR, PWR, and PLR are new prognostic indicators in neurological disorders. 19 , 20 To our knowledge, this study is the first to explore the impact of these inflammation markers on the development of ABS associated with ASDH. The multivariate analysis revealed that low PWR on admission was an independent risk factor for post-traumatic ABS.…”
Section: Discussionmentioning
confidence: 95%
“…Considerably, TBI patients with coagulopathy have more severe brain injuries and vigorous inflammatory reactions than those without coagulopathy signs. 41 Therefore, Alexiou et al introduced the value of NLR as a predictive biomarker for coagulopathy in TBI patients with a cut-off value of 4.2. 42 Lattanzi et al also demonstrated that higher levels of NLR in patients with spontaneous intracerebral hemorrhage within 24 h from onset were independently accompanied with more 30 days mortality and morbidity.…”
Section: Main Textmentioning
confidence: 99%